2021
DOI: 10.1007/s40588-021-00156-w
|View full text |Cite
|
Sign up to set email alerts
|

Physical Methods for the Decontamination of Meat Surfaces

Abstract: Purpose of Review The market for minimally processed products is constantly growing due to consumer demand. Besides food safety and increased shelf life, nutritional value and sensory appearance also play a major role and have to be considered by the food processors. Therefore, the purpose of the review was to summarize recent knowledge about important alternative non-thermal physical technologies, including both those which are actually applied (e.g. high-pressure processing and irradiation) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 112 publications
0
12
0
Order By: Relevance
“…Beside the more conventional curing methods, irradiation [ 66 ], pressure [ 67 ], and active packaging [ 68 , 69 , 70 ] are methods that are frequently used in an industrial production process. Since these methods appear very exotic for consumers, a PPA treatment is analogous to an ordinary curing method that might be advantageous for consumer acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…Beside the more conventional curing methods, irradiation [ 66 ], pressure [ 67 ], and active packaging [ 68 , 69 , 70 ] are methods that are frequently used in an industrial production process. Since these methods appear very exotic for consumers, a PPA treatment is analogous to an ordinary curing method that might be advantageous for consumer acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…Although ultrasonication technology has been proven safe and effective for water purification and decontamination of carcasses and meat surfaces, numerous studies indicated that its application to Campylobacter -contaminated chicken meat and skin did not significantly reduce Campylobacter numbers. Detailed information on the effectiveness of other physical and chemical methods to reduce the concentration of Campylobacter on chicken carcasses during the slaughter process have been reviewed elsewhere [ 192 , 202 ].…”
Section: Post-harvest Control Measures (Production Chain Interventions)mentioning
confidence: 99%
“…These possibilities include the use of organic acids, peroxyacetic acid, chlorine, carbon dioxide, acidic calcium sulfate, activated lactoferrin, cetylpyridium chloride, ozone, essential oils and plant extracts, bacteriophages, bacteriocins, intelligent packing, high-pressure processing, ultrasound, irradiation, pulsed electric field (Sohaib et al, 2016), ultraviolet light, photodynamic inactivation (Corrêa et al, 2020), pulsed light, and cold atmospheric plasma (Albert et al, 2021).…”
Section: Meat Contamination and Strategies For Its Decontaminationmentioning
confidence: 99%
“…These practices can reduce meat contamination, and their adoption has been frequently recommended; however, chemical, physical, and biological strategies focused on decontaminating meat have also been proposed and used as a complementary approach. These possibilities include the use of organic acids, peroxyacetic acid, chlorine, carbon dioxide, acidic calcium sulfate, activated lactoferrin, cetylpyridium chloride, ozone, essential oils and plant extracts, bacteriophages, bacteriocins, intelligent packing, high‐pressure processing, ultrasound, irradiation, pulsed electric field (Sohaib et al, 2016), ultraviolet light, photodynamic inactivation (Corrêa et al, 2020), pulsed light, and cold atmospheric plasma (Albert et al, 2021).…”
Section: Meat Contamination and Strategies For Its Decontaminationmentioning
confidence: 99%